The Role of Educational Technology in Enhancing Students’ Literacy and Numeracy through the AKM Assessment in the Kampus Mengajar Program - Sinta Ulina Situmorang (Jurnal Pendidikan Vokasi Indonesia, 2025)
Literacy refers to the fundamental knowledge required by students to comprehend written texts, while numeracy denotes the ability to understand and apply numerical concepts in everyday life. To assess students' literacy and numeracy skills, it is necessary to administer standardized tests. This study aims to analyze the literacy and numeracy competencies of fifth-grade students at SDN 101914 Kampung Baru through the implementation of the Minimum Competency Assessment (Asesmen Kompetensi Minimum/AKM), as part of the Kampus Mengajar Batch 6 program. The AKM test was conducted in two stages: (1) a pretest for both literacy and numeracy, and (2) a posttest for both domains. The data obtained were analyzed using descriptive statistical methods to calculate students' average scores. The findings indicate that the Kampus Mengajar program contributed to improvements in students' literacy and numeracy skills. This is evidenced by an increase in correct responses, with literacy scores rising from 47% in the pretest to 69% in the posttest, and numeracy scores increasing from 27% to 50%. These results suggest that the intervention supported both student learning outcomes and educational innovation.